2021
DOI: 10.1097/md.0000000000027664
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic medication prescribing during the COVID-19 pandemic

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
0
26
3
1
Order By: Relevance
“…Our findings contrasted the results of a cross-sectional study where the investigators found no clinically meaningful differences in overall prescription rates of psychotropic medications in 2020, compared to 2019, using data from Kaiser Permanente Northern California electronic records ( Hirschtritt et al, 2021 ). After accounting for secular trends or prior year patterns, they found a small, but significant increase in the antidepressant trazodone and mood stabilizers/antipsychotics, and a small decrease in benzodiazepines and hypnotics, with no significant change in antidepressants and stimulants ( Hirschtritt et al, 2021 ). They also found a lower-than-expected trend in new fills for nearly all medications, including antidepressants, benzodiazepines, hypnotics, and mood stabilizers and antipsychotics ( Hirschtritt et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our findings contrasted the results of a cross-sectional study where the investigators found no clinically meaningful differences in overall prescription rates of psychotropic medications in 2020, compared to 2019, using data from Kaiser Permanente Northern California electronic records ( Hirschtritt et al, 2021 ). After accounting for secular trends or prior year patterns, they found a small, but significant increase in the antidepressant trazodone and mood stabilizers/antipsychotics, and a small decrease in benzodiazepines and hypnotics, with no significant change in antidepressants and stimulants ( Hirschtritt et al, 2021 ). They also found a lower-than-expected trend in new fills for nearly all medications, including antidepressants, benzodiazepines, hypnotics, and mood stabilizers and antipsychotics ( Hirschtritt et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 98%
“…After accounting for secular trends or prior year patterns, they found a small, but significant increase in the antidepressant trazodone and mood stabilizers/antipsychotics, and a small decrease in benzodiazepines and hypnotics, with no significant change in antidepressants and stimulants ( Hirschtritt et al, 2021 ). They also found a lower-than-expected trend in new fills for nearly all medications, including antidepressants, benzodiazepines, hypnotics, and mood stabilizers and antipsychotics ( Hirschtritt et al, 2021 ). This was consistent with our findings of a decline in incidence in antidepressants and anxiolytic/sedative-hypnotic use in the second quarter as their data were only limited to the first 13 weeks of the pandemic in California.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations may be postulated including the drop in medical consultations in this age group during the pandemic for all health problems, including mental health (e.g. Hirschtritt, Slama, Sterling, Olfson, & Iturralde, 2021 ; ONS, 2021c ), despite the significant increase in mental health problems reported by older individuals (Tyler et al, 2021 ). For individuals aged 65 years or older, difficulties accessing telehealth may act as a substantial barrier (Lam, Lu, Shi, & Covinsky, 2020 ) because of unfamiliarity with the relevant technology.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our analyses were limited to one class of psychotropics (i.e. antidepressants) but there is some evidence that prescriptions of all psychotropics may have increased during the pandemic (Express Scripts, 2020 ; Hirschtritt et al, 2021 ). Further, we did not collect information on the different types of antidepressants prescribed or other forms of treatment such as psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies suggested that selective serotonin reuptake inhibitors, serotonin–norepinephrine reuptake inhibitors, and the SARI classes of antidepressants drove this protective effect on COVID-19 infection risk [ 32 , 33 ]. Furthermore, it has been shown that during the COVID-19 pandemic—specifically in the 13 weeks following March 4, 2020—there were increased prescriptions in adult patients for trazodone, and decreased prescriptions for benzodiazepines and hypnotics [ 34 ]. This may reflect a shift in clinicians’ attitudes and increased awareness of trazodone’s actions.…”
Section: Discussionmentioning
confidence: 99%